Children's exposure to food advertising: An analysis of the effectiveness of self-regulatory codes in Australia - Roberts, M.; Pettigrew, Simone; Chapman, K.; Quester, P.; Miller, C. (Wiley-Blackwell Publishing Asia, 2014)
Aim: The aim of this study was to update knowledge about children’s exposure to televised food advertising in Australia, providing a more comprehensive examination of children’s exposure since the introduction of selfregulatorycodes.Methods: Two months of food advertisement data from four free-to-air television stations (SBS, Seven Network, Nine Network and Ten Network) in the five largest Australian cities (Sydney, Melbourne, Brisbane, Adelaide and Perth) were purchased and analysed. A content analysis was performed to classify the advertised products into food groups according to the Australian Guide to Healthy Eating and whether they were scheduled in children’s popular viewing times (CPVT) according to audience viewing data from OzTam. They were also assessed as to whether theyincluded a premium offer (free incentive). The 2 months of data covered September and October 2010 and included 43 weekdays, 18 weekend days and 15 days of school holidays.Results: In total, 93 284 food advertisements, including repeat airings, were analysed from 1464 hours of continuous programming. The majority (63%) included non-core foods. During CPVT, this figure was significantly higher at 65% versus 61% outside CPVT. Within CPVT, the percentage of advertisements was higher for quick-service restaurants (30% vs 26%) and unhealthy beverages (3% vs 2%). Fifteen per cent of all advertisements were for sugar-sweetened soft drinks. Premiums were still apparent (10% vs 8%) despite being restricted by the codes.Conclusions: Australian children continue to be exposed to a large amount of advertising for non-core foods, despite the introduction of voluntary codes.